Pro-environmental actions of agricultural farms - example of holdings from the Wielkopolska region = Działania prośrodowiskowe gospodarstw rolnych - przykład gospodarstw z Wielkopolski - Grzelak, Aleksander; Borychowski, Michał; Staniszewski, Jakub (Zielona Góra: Faculty of Economics and Management Press)
The main aim of the article is to identify pro-environmental actions in farms in the Wielkopolska region. The article uses the results of surveys carried out in 2020 in a group of 120 agricultural holdings from Wielkopolska running agricultural accounting according to the FADN (Farm Accountancy Data Network) system. The time scope of the analyses referred to the period 2016-2019, and in the case of economic data to 2018.
Keywords: farm; environment; incomes; Wielkopolska - region; pro-environmental activity; gospodarstwo rolne; środowisko; dochody; Wielkopolska; aktywność prośrodowiskowa